ANALISIS KEUNTUNGAN USAHA â€œSARABAâ€ DI RUMAH MAKAN STEVANNY DI KAWASAN BOULEVARD KOTA MANADO - Priscilia Indriani Runturambi; Ribka Magdalena Kumaat; Juliana Ruth Mandei (AGRI-SOSIOEKONOMI, 2018)
This study aims to analyze the profit received by the owner, producer and seller of the business "Saraba" in "Stevanny Restaurant" in the Boulevard Area of Manado City. This research was conducted from July to September 2018. This study used primary data and secondary data. Primary data was obtained by using interview techniques directly to the owner of the restaurant. Secondary data in this study comes from books available at local bookstores in Manado City, the internet such as google scholar to access articles from various scientific journals and theses from other universities which was related to profit analysis. Data collected in this study are presented in table form and then described and analyzed using the profit analysis formula. The results showed that the profits obtained in one month of the production process in September 2019, which is for 30 days where every day one production process is carried out so 30 days the production process is carried out by the businessman "Saraba" in "Stevanny's Restaurant" in the Boulevard Area of Manado City for Rp. 5,609,481 per month.*jnkd+eprm*.